MOOCs, High Technology, and Higher Learning - Rhoads, Robert A. (Book collections on Project MUSE., 2015)
"In MOOCs, High Technology, and Higher Education, Rob Rhoads seeks to put the OpenCourseWare (OCW) movement into a larger context that culminates in the introduction of Massively Open Online Courses (MOOCs). This book highlights a particular moment in history when cultural, political, and economic forces came together to bring about the MOOC as a unique educational innovation. In addition to defining MOOCs apart from other online course systems, Rhoads offers a provocative description of the various learning cultures and methods that continue to stimulate and expand the demand for MOOCs as a social movement in higher education. The methodology undergirding this book combines critical discourse analysis of key documents and publications as well as empirical studies of MOOC-related issues, including studies of MOOC content delivery, the organizational system supporting the OCW/MOOC movement, and faculty labor concerns"--